2013
DOI: 10.2174/092986713805219082
|View full text |Cite
|
Sign up to set email alerts
|

The Pentacyclic Triterpenoids in Herbal Medicines and Their Pharmacological Activities in Diabetes and Diabetic Complications

Abstract: Pentacyclic triterpenoids including the oleanane, ursane and lupane groups are widely distributed in many medicinal plants, such as Glycyrrhiza species, Gymnema species, Centella asiatica, Camellia sinensis, Crataegus species and Olea europaea, which are commonly used in traditional medicine for the treatment of diabetes and diabetic complications. A large number of bioactive pentacyclic triterpenoids, such as oleanolic acid, glycyrrhizin, glycyrrhetinic acid, ursolic acid, betulin, betulinic acid and lupeol h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
86
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 209 publications
0
86
0
3
Order By: Relevance
“…The n-hexane fraction of Myagropsis myagroides showed significant amylase inhibition [32]. Saleh et al (2013) observed significant α-glucosidase and α-amylase inhibitory in the n-hexane fractions of ten plant extracts traditionally used in Iran for diabetes [33,34].…”
Section: α-Amylase and α-Glucosidase Inhibition Studiesmentioning
confidence: 99%
“…The n-hexane fraction of Myagropsis myagroides showed significant amylase inhibition [32]. Saleh et al (2013) observed significant α-glucosidase and α-amylase inhibitory in the n-hexane fractions of ten plant extracts traditionally used in Iran for diabetes [33,34].…”
Section: α-Amylase and α-Glucosidase Inhibition Studiesmentioning
confidence: 99%
“…UA has been shown to exert many beneficial effects such as anti-diabetes [36], anti-obesity [37], and anti-cancer [38]. Several recent studies show that UA exerts its anti-tumor role through inhibition of the mTOR signaling pathway [39], suggesting a potential mechanism underlying the beneficial effects of UA.…”
Section: Discussionmentioning
confidence: 99%
“…Betulinic acid, a pentacyclic triterpenoid, is widely found in the medicinal plants (Gauthier et al, 2011), including Bacopa monniera Diospyros bipindensis (Viji et al, 2010), (Brusotti et al, 2017), (James and Dubery, Centella asiatica 2009), (Qian et al, 2012) etc. Betulinic acid Zizyphi spinosi was reported to have a wide spectrum of pharmacological activities such as, antioxidant (Yamashita et al, 2002), antiinflammatory (Viji et al, 2010), antimalarial (de Sá et al, 2009, antidiabetic (Alqahtani et al, 2013), antidepressant (Machado et al, 2013), anti-HIV (Fujioka et al, 1994), antihepatitis C (Lin et al, 2015), antineoplasic (Fulda, 2009) and immunomodulatory activities (Pang et al, 2018). In addition, betulin or its bioactive derivative betulinic acid showed neuroprotective effects in cerebral ischemiareperfusion injury (Lu et al, 2011), Parkinson's disease (Tsai et al, 2017), epilepsy (Muceniece et al, 2008), amyloid beta-induced neurotoxicity (Planchard et al,2012) and multiple sclerosis (Blazevski et al, 2013).…”
Section: Introductionmentioning
confidence: 99%